Nanoparticles in life sciences and biomedicine - Neves, Ana Rute; Reis, Salette (Pan Stanford Publishing, 2018)
The creation of new and more efficient therapies for improving human health greatly depends on drug delivery systems. Nanotechnology has emerged as a powerful strategy for the development of nanoparticles, such as nanoemulsions, liposomes, nanocrystals, and nanocomplexes, applied in the diagnosis, treatment, or theranostics of several pathologies and diseases. This book reviews the most recent research and development in nanotechnology and, following a multidisciplinary approach, presents new strategies for drug delivery, including aspects from chemistry, physics, biology, and imaging methodologies and exploiting several administration routes, internalization pathways, site-specific delivery strategies, and the potential cytotoxicity of nanoparticles.